Thanatophoric dysplasia: a rare entity - Arya, Sangeeta; Pandey, Kiran; Gupta, Disha; Pande, Shefali (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2016)
Thanatophoric dysplasia (TD), a rare and lethal skeletal dysplasia of neonatal period. Two clinical forms of Thanatophoric dysplasia have been described. TD is caused by specific autosomal dominant mutations in the gene that codifies for the Fibroblast Growth Factor Receptor 3 (FGFR3). The mutations constitutively activate the tyrosine kinase activity of the receptor. The estimated birth incidence is approximately 1/20,000 to 1/50,000. TD I being more frequent than TD II. Most individuals with TD die within the first few hours or days of life. Currently, specific therapeutic regiments do not exist. Prenatal diagnosis is available, both by ultrasonography and by molecular studies. This case report describes fetus with one of this rare disorder.